AIM2 levels and DNA-triggered inflammasome response are increased in peripheral leukocytes of patients with abdominal aortic aneurysm - Wortmann, Markus; Xiao, Xianghui; Wabnitz, Guido H.; Samstag, Yvonne; Hakimi, Maani; Böckler, Dittmar; Dihlmann, Susanne (Inflammation research, 2019)
Objective and designAbdominal aortic aneurysm (AAA) is heavily infiltrated with leukocytes, expressing the DNA sensor absent in melanoma 2 (AIM2) and other inflammasome components.MethodsUsing multicolour flow cytometry, we here compared the expression of the inflammasome components AIM2, NLRP3, and ASC in different peripheral immune cells derived from AAA patients with those from non-AAA patients in a case-control study. In parallel, peripheral blood mononuclear cells (PBMC) of AAA patients and controls were stimulated in vitro with poly-dA:dT or lipopolysaccharide (LPS) to analyze inflammasome activation.ResultsAIM2 expression was significantly increased in peripheral granulocytes (P = 0.026), monocytes (P = 0.007), B lymphocytes (P < 0.0001), and T lymphocytes (P = 0.004) of AAA patients. Expression of other inflammasome components did not differ between the groups. Following in vitro stimulation with foreign DNA, PBMC derived from AAA patients released significantly more IL-1β (P = 0.022) into the supernatant than PBMC from control patients. In contrast, IL-1β release upon LPS stimulation did not differ between the PBMC groups.ConclusionThe data indicate the increased activation of an AIM2 inflammasome in peripheral immune cells of AAA patients and point to a systemic AIM2-associated immune response to AAA.